Global Commodity Chains and the New Imperialism - Bellamy Foster, John; Jonna, Jamil; Suwandi, Intan (Revista Internacional de Salarios Dignos, 2020)
Jus Semper’s core work has been from inception assessing the enormous disparities in hourly manufacturing labour costs, for equivalent work, between the metropolises and the emerging economies in the periphery of the global system. We have always performed our work for reasons of equity, using purchasing power parity compensation costs, under the context of equal pay for equal work of equal value We do this to expose the sheer exploitation of labour in peripheral economies for the maximisation of productivity and shareholder value of global corporations. In this way, we have published our annual reports on “Wage rate gaps for selected developed and emerging economies in manufacturing” since 2003, using data dating back to 1975.